A VLSI Image Processing Algorithm for Biomedical Applications - Kumari, Pilli.Lalitha; Rajani, Alugonda; Sanyasi Rao, Allanki (International Journal of Scientific Methods in Engineering and Management, 2023)
The domain of signal processing that is dedicated to applications in the medical sector has shown phenomenal expansion over the course of the last decade. It’s possible that developments in fields such as computer-aided design (CAD), healthcare, and automated signal processing have played a key part in this expansion. As a result of the current COVID-19 epidemic, there is a greater need for biomedical signal analysis, and from an imaging point of view, biomedical research projects far exceed those that use more basic signal processing methodologies. The fundamentals of image processing and the processing of biological pictures have been the subject of a lot of studies, and the findings of these studies have shown a variety of possible applications in a variety of settings. A examination of the existing literature reveals that there are a limited number of solutions that are based on very large scale integration (VLSI). As a direct consequence of this, this chapter devotes a significant amount of its focus to the investigation of biological image processing, particularly in terms of its applications and VLSI implementations. It is hoped that researchers and investigators would find this useful in better preparing a solution to this issue so that it may be put into action. Following an analysis of the most recent developments in research, a number of possible directions for future research have been contemplated.